Perceptual discrimination and categorization of vowels in different levels of foreign language instruction - Ane Icardo Isasa (Anuario del Seminario de Filología Vasca "Julio de Urquijo")
This paper reports on the development of L2 English vowel pair perception by adult L1 Spanish/Basque speakers of differing levels of English instruction. This study focuses on vowel pairs /i-ɪ/, /u-ʊ/ and /ʌ-ɔ/, with differing levels of proximity to native categories. Results of two perceptual tasks show that learners are influenced by their native categories, but that regardless of level, they can still modify their representations. However, the success in categorization varies by sound based on acoustic distance and multiple category competition.